2022
DOI: 10.1039/d2qo00236a
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of Cu-catalyzed 1,2-hydrocarboxylation of 1,3-dienes with CO2: Pauli repulsion-controlled regioselectivity of Cu–Bpin additions

Abstract: The mechanism and origin of regioselectivity of Cu-catalyzed 1,2-hydrocarboxylation of 1,3-dienes with CO2 were computationally investigated. The results show that CO2 not only acts as a carboxylation reagent, but also...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…12 1,3-Dienes are readily accessible chemicals and direct C–H bond allylation with 1,3-dienes, as an atom economical process, has been well studied. 13 However, the regioselective C–H bond allylation of phenols with 1,3-dienes has seen far less exploration, with only two examples reported to date. In a seminal study reported by Li and coworkers in 2019, ortho -selectivity was obtained by B(C 6 F 5 ) 3 catalysis (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…12 1,3-Dienes are readily accessible chemicals and direct C–H bond allylation with 1,3-dienes, as an atom economical process, has been well studied. 13 However, the regioselective C–H bond allylation of phenols with 1,3-dienes has seen far less exploration, with only two examples reported to date. In a seminal study reported by Li and coworkers in 2019, ortho -selectivity was obtained by B(C 6 F 5 ) 3 catalysis (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The transmetalation of borone ester and copper salt produced allylic copper species, which reacted with CO 2 to deliver the corresponding acid products. Very recently, the mechanism and origin of regioselectivity of this reaction were computationally investigated by Lu and co‐workers [40] . As a carboxylation reagent, CO 2 in the reaction also facilitated to generate the key allyl copper intermediate.…”
Section: Copper‐catalyzed Carboxylation Of C−c Double Bondsmentioning
confidence: 99%
“…Very recently, the mechanism and origin of regioselectivity of this reaction were computationally investigated by Lu and co-workers. [40] As a carboxylation reagent, CO 2 in the reaction also facilitated to generate the key allyl copper intermediate.…”
Section: Carboxylation Of Dienesmentioning
confidence: 99%